Dynamic voltage restorer using the combination of fuzzy logic and EPLL control strategies: An optimized implementation - Taghizadeh S.F.; Tan N.M.L.; Nikouei B.; Younis M.A.A. (IEEE Computer Society, 2023)
Voltage sag is the most frequent power quality disturbance and it must be mitigated to protect sensitive electronic devices such as adjustable speed drives and programmable logic controllers. Dynamic voltage restorer (DVR) is introduced as an effective solution to mitigate voltage sag appeared on distribution lines. This paper considers the operation of a dynamic voltage restorer for voltage sag mitigation. This paper proposes a control system using the combination of enhanced phase lock loop (EPLL) and fuzzy logic (FL). The simulation results using EMTDC/PSCAD software show the reliability and speed of the proposed system in terms of voltage sag detection and synchronization time during different types of voltage sags. © 2014 IEEE.